Empatia de enfermeiras em UTIN - Mufato, Leandro Felipe (2019)
ABSTRACT: The philosophical and scientific debate about empathy reemerges nowadays. It has become an interesting phenomenon to be studied by qualitative health research, especially with patients with specific characteristics, such as newborns in Neonatal Intensive Care Units (NICU) and their relatives. This thesis started from the following questions: how is the experience of empathy for nurses in a neonatal intensive care unit? What is the essence of the empathic experience faced by nurses in neonatal intensive care units? How does the structure of the experience of empathy influence the relations among nurses, neonates and relatives? Objective: to understand the experience of empathy faced by nurses with neonates and their relatives in NICU. Justification: there is a need for investments in research that deals with the humanization of neonatal nursing care, as it can be seen that human professional conduct is still a challenge amid the technological advances in NICU services. Theoretical lens: phenomenology based on David Cerbone, Alfred Schutz and Dan Zahavi. Methodology: hermeneutic phenomenological research underpinned by Max van Manen, carried out at the NICU of a University Hospital, located in Cuiabá, with 11 nurses. We made use of open interviews with questions such as: “Could you tell me what you have faced regarding empathy when caring for neonates and their relatives?”. These interviews were held between May and August 2018, and then transcribed in a Field Diary, which were analyzed according to the framework of Max van Manen’s thematic analysis, obtaining an understanding of the experiences related to empathy. The themes identified were: The empathy of nurses with babies: what is perceived; The empathy of nurses with babies: empathic behavior; The empathy of nurses with babies’ relatives: what is perceived; The empathy of nurses with babies’ relatives: empathic behavior; Other experiences that influence the empathy of nurses in neonatal ICU; The place that empathy occupies in neonatal nursing care. After the analysis, we performed a comprehensive synthesis of the nurses’ experiences, followed by their understanding in the light of phenomenology. Results: for the surveyed nurses, empathy is an affective experience, started by their mobilization by the baby in the incubator and the baby who receives or not the affection of the mother, emerging as a way of making the other being special in the perception of these nurses. There is a centrality when acting with their own bodies towards the babies as well as in the welcoming and dialogue with the mothers. The experiences of the nurse in her own family core, her experience as a mother, daughter and mother of a baby admitted to the NICU, besides having faced family losses, influence the experience of empathy. NICU administrative and clinical demands interfere with nursing care, making empathy with babies and their mothers dependent on the nursing professional. Final considerations: the understanding of the experience of empathy for nurses allows us to analyze how it is understood or not as relevant to their work, even though it is considered fundamental for humanization in nursing care in NICU environments.